Social Integration of Syrian Male Refugees in Finland - Matveeva, Iuliia (My University, 2016)
This study explores the process of social integration of Syrian male refugees in Finland. The thesis belongs to the field of forced migration studies and human geography. The main research aim is to evaluate the dynamics of the social integration process. The complex terms of social capital and social inclusion define the cornerstones of the social integration of forced migrants. The course of integration is hampered by different obstacles that undermine the natural flow of being included into society by creating rich social capital. The empirical data was gathered by conducting semi-structured interviews with Syrian male refugees, there were two groups of respondents: oldcomers and newcomers. The data is analyzed qualitatively by using qualitative content analysis. Through my analysis I discover the roots of the obstacles into being socially integrated. Discrimination and ignorance, emotional traumas and poor policy of multiculturalism in Finland are discussed as the major challenges in the dynamic process of social integration.